The model of evaluating the performance of the employees of the Islamic Republic of Iran Army in joint operations - Majid Rashidi; Mohammad Shahmohammadi; Omid Ardalan; Ali Niyazi (علوم و فنون نظامی)
The employee performance evaluation model is a very complex, sensitive process and has a special place in the AJA headquarters, and considering that the future wars are mainly based on joint operations, the designers of military operations should use all the capacities of the real battlefields, including air, space, land and sea for to achieve victory and inflict heavy damage on the other party. The main purpose of this research is to design a model for evaluating the performance of the employees of the Islamic Republic of Iran Army in joint operations, and the research method is descriptive and of an applied development type. The statistical population for the qualitative part includes 10 experts, commanders and managers of strategic levels of AJA and 45 people for the quantitative part.To determine the sample population in the qualitative part, the whole number method and in the quantitative part, the distance estimation method of the mean was used. The data collection tool is library and field study. The experiences of professors and expert community were used for the validity of documents, interviews and questionnaires, and spss software and Cronbach's alpha calculation were used to measure validity.The results of this research show that performance evaluation is one of the most effective monitoring tools for efficiency, empowerment and development and improvement of individual and organizational performance and is associated with meritocracy and meritocracy, meritocracy, meritocracy, and accordingly, meritocracy and the creation of healthy classes. And fair relations motivate managers and employees to work hard